Gender differences in competition emerge early in life - Matthias Sutter; Daniela Rützler (Institute for the Study of Labor (IZA), 2010)
We study gender differences in the willingness to compete in a large-scale experiment with 1,035 children and teenagers, aged three to eighteen years. Using an easy math task for children older than eight years and a running task for the younger ones we find that boys are much more likely to enter a tournament than girls across the whole age spectrum considered here. This gender gap is observed already with three-year olds, indicating that gender differences in competitiveness emerge very early in life. The gap is robust to controlling for gender differences in risk attitudes and overconfidence.
Keywords: C91; D03; 330; Competition; gender gap; experiment; children; teenagers; Verhaltensökonomik; Wettbewerb; Geschlecht; Kinder; Test